2003
DOI: 10.1088/0953-4075/36/10/201
|View full text |Cite
|
Sign up to set email alerts
|

Strong-field atomic stabilization: numerical simulation and analytical modelling

Abstract: The phenomenon of strong laser field atomic stabilization is discussed. Earlier suggested models and mechanisms of stabilization are described: Λ- and V-type interference stabilization of Rydberg atoms, adiabatic (Kramers–Henneberger) and high-frequency stabilization of neutral atoms and negative ions, and so on. Both numerical and analytical approaches to the description of these phenomena are discussed. In this context, ab initio numerical solutions of the nonstationary Schrödinger equation, obtained by seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 112 publications
2
69
0
Order By: Relevance
“…and ε 0 > 8 a.u. This is the well-known strong-field atomic stabilization phenomenon [66][67][68][69][70][71][72]. This phenomenon can occur at any frequency and can be enhanced by relativistic effects [70].…”
Section: Fig 2 (Color Online)mentioning
confidence: 98%
See 1 more Smart Citation
“…and ε 0 > 8 a.u. This is the well-known strong-field atomic stabilization phenomenon [66][67][68][69][70][71][72]. This phenomenon can occur at any frequency and can be enhanced by relativistic effects [70].…”
Section: Fig 2 (Color Online)mentioning
confidence: 98%
“…This phenomenon can occur at any frequency and can be enhanced by relativistic effects [70]. Detailed discussions about the strong-field atomic stabilization and various physical mechanisms have been given in recent review papers [71,72].…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%
“…For typical ω's considered in this work, e.g. 2-3, the outershells satisfy ω > I p where we expect stabilization, while innershell electrons can be excited to Rydberg states by multiphoton absorption and subsequently be stabilized [28,29]. Now consider b).…”
Section: Spectramentioning
confidence: 93%
“…It therefore came as a big surprise to many when, more than 20 years ago, theoretical studies of atomic hydrogen in ultraintense, high-frequency laser fields showed some evidence of the complete opposite scenario, i.e., that the atom may eventually become more stable as the ionizing radiation gets stronger [3][4][5][6][7][8][9][10][11]. This rather counterintuitive phenomenon, called atomic stabilization, has since then been studied extensively; see, e.g., [12][13][14][15] and references therein. It has also been argued that atomic stabilization has a classical counterpart [16,17].…”
Section: Introductionmentioning
confidence: 99%